SIMULASI SERANGAN SIBER MAC ADDRESS DAN IP ADDRESS SPOOFING PADA JARINGAN HTTP DI KALI LINUX - Muhammad Rizki Andrian Fitra; Neysa Talitha Jehian; Lastri Elisabet Butarbutar; Dedy Kiswanto (Jurnal Teknologi Informasi dan Komputer, 2025)
The rapid development of information technology presents a big challenge in terms of network security, especially against cyber-attacks. This research simulates MAC Address Spoofing attack on HTTP network using Kali Linux operating system. The purpose of this research is to understand how the attack process is carried out and evaluate its impact on communication security in an unencrypted network. The attacker impersonated a gateway through ARP Spoofing technique and successfully infiltrated the communication path between the victim and the server. The captured data shows that sensitive information such as usernames and passwords can be easily retrieved when the victim accesses HTTP sites. The results show that spoofing has been successfully carried out, as evidenced by the acquisition of usernames and passwords when victims access HTTP sites.